The study of structure and effects of two new proanthocyanidins from Anogeissus pendula leaves on rumen enzyme activities - Lata, Suman; Koli, Pushpendra; Singh, Sultan; Bhadoria, B. K.; Chand, Umesh; Ren, Yonglin (Frontiers in Veterinary Science, 2023)
Two novel proanthocyanidins, (2R, 3R)-(+)-Gallocatechin-(4β→8)4-(2R, 3R)-(+)-gallocatechin (compound 1) and 3-O-galloyl-(2S, 3S)-(−)-epicatechin-(4α→8)-[3-O-galloyl-(2S, 3S)-(−)-epicatechin (4α→8)]2-(2S, 3S)-(−)-epicatechin (compound 2), were structurally characterized from leaves of Anogeissus pendula. The structures were determined by ultraviolet spectroscopy (UV), proton nuclear magnetic resonance (1H NMR), 13C NMR and Heteronuclear multiple bond correlation. Molinspiration and Osiris property explorer applications were used to predict bioactivity and drug score. Drug scores of 0.08 and 0.05 were predicted for compounds 1 and 2, respectively. Predicted bioactivity-scores were high. The novel proanthocyanidins have an affinity for interaction with proteins due to MW, chemical structure, and conformation. With this in mind, both compounds were tested against ruminal enzymes in vitro. They exhibited significant inhibition activities (p < 0.01) with a range of half maximal effective concentration (EC50) of 14.80-17.88 mg/mL of glutamic oxaloacetic transaminase in both protozoa and bacteria fractions. The ruminal glutamic pyruvic transaminase activity was significantly inhibited (p < 0.01) from EC50 12.59-16.29 mg/mL, and R-cellulase inhibition was recorded with EC50 18.20-21.98 mg/mL by compounds 1 and 2, respectively. Protease activity decreased with increasing incubation time and concentration of both compounds. The novel proanthocyanidins have potential roles in improving feed conversion ratios and in drug development.